Reactualization of the Takrir Method in Learning Al-Qur'an Memorization Amidst the Declining Quality of Students' Muraja'ah - Syofrianisda, Syofrianisda; Tamsik Udin; Juliwis Kardi (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2024)
Memorizing the Quran is a characteristic of Islamic boarding school students. However, many students are still negligent in improving their memorization, so they do not reach the target. This dynamic is compounded by the inappropriate use of learning methods. The takrir method is a method used in learning to memorize the Quran by repeating verses until they are memorized. The takrir method is able to increase the quantity of students' memorization. Thus, this study is intended to answer the problem of how guidance by tahfidz teachers in applying the takrir method to improve the memorization of students at the Darul Mursyidin Islamic Boarding School. This study uses a qualitative method with a case study approach, data sources are taken through individual and group interviews with seven informants selected using a purposive sampling technique, the informants in question are the principal, teachers and students. In-depth interviews were conducted with students who memorize the Quran. The results of this study are: 1) Coaching by tahfidz teachers using the takrir method to improve students' memorization is carried out through several stages, namely submitting new memorization to ustadzah, joint takrir, individual takrir, takrir in prayer and additional studies such as the study of the book Tafsir ayat Ahkam, At-Tibyan and Tajwid 2) Supporting factors in Coaching by tahfidz teachers in applying the takrir method to improve students' memorization at the Darul Mursyidin Islamic Boarding School are asking for blessings from parents. According to researchers, asking for blessings from parents is very important because it is one of the things that can make a memorizer enthusiastic. 3) Inhibiting factors for the development of tahfidz teachers in applying the takrir method to improve the memorization of students at the Darul Mursyidin Islamic Boarding School. The obstacles felt by the students of the Darul Mursyidin Islamic Boarding School are: laziness, fatigue, illness and so on. Among the solutions are self motivation, adequate rest, istiqamah and so on. Improving the memorization of students is important and the takrir method is the right method.